Water-mediated modulation of TiO2 decorated with graphene for photocatalytic degradation of trichloroethylene - Lee, Dong-Su; Park, Soo-Jin (Current applied physics, 2015)
The improvement of photocatalytic properties of TiO2 was achieved by using water-mediated TiO2 decorated with graphene (WTiO2-d-graphene) composites. This work describes the photocatalytic degradation of trichloroethylene (TCE) in the presence of WTiO2-d-graphene composites. WTiO2-d-graphene composite photocatalysts, containing different amounts of graphene, were prepared by facile ultrasonic assisted techniques and thermal reaction. The surface properties of these WTiO2-d-graphene composites were characterized by X-ray photoelectron spectroscopy (XPS). Peaks attributable to C–C (284.4 eV), denoted as the C1s spectrum, and C–O bonds (288.6 eV) appeared simultaneously in the XPS spectrum. It was inferred that this was due to the presence of Ti–O–C bonds. The photocatalytic properties were determined by monitoring the degradation of TCE in the headspace of the vial at different times using gas chromatography. From the results, it was apparent that the photocatalytic activities of WTiO2-d-graphene composites were higher than that of pure TiO2. This can be attributed to their ability to absorb light over a wider range of wavelengths. Schematic illustration of the synthetic route for WTiO2-d-graphene composites. [Display omitted] •WTiO2-d-graphene composites was accomplished via a thermal reaction.•WTiO2-d-graphene composites absorb over a wide wavelength range.•The photocatalytic activities of WTiO2-d-graphene composites were higher than that of pure TiO2.